Prevalence of osteoporosis according to nutrient and food group intake levels in Korean postmenopausal women: using the 2010 Korea National Health and Nutrition Examination Survey Data - Lim, Y.S., Myongji University, Yongin, Republic of Korea; Lee, S.W., Myongji University, Yongin, Republic of Korea; Tserendejid, Z., Myongji University, Yongin, Republic of Korea; Jeong, S.Y., Myongji University, Yongin, Republic of Korea; Go, G., Myongji University, Yongin, Republic of Korea; Park, H.R., Myongji University, Yongin, Republic of Korea (Nutrition research and practice, 2015)
BACKGROUND/OBJECTIVES: Womens bone health status is closely related with environmental factors and lifestyle factors. The purpose of this study is to evaluate the dietary risks of osteoporosis and osteopenia for Korean postmenopausal women. SUBJECTS/METHODS: The data from 1,433 subjects from the 2010 KNHANES were used and divided into three groups: normal, osteopenia, and osteoporosis group using bone mineral density (BMD). Nutrient intakes and food intake frequency were evaluated. Logistic regression analysis was applied to determine the odds ratios for osteoporosis and osteopenia. RESULTS: The RNI percentage of each nutrient and food intake frequency from 12 food groups decreased as bone mineral density status deteriorated. Risk for osteoporosis of low calcium (Ca) intake, under the EAR, showed an odds ratio of 2.13(95% CI; 1.26-3.61, P 0.05). Higher intake frequency showed preventive effect from osteoporosis compared to lower intake frequency in such food group as dairy products (ORs 0.40, CI 0.21-0.75), beans (ORs 0.49, CI 0.29-0.83), seaweeds (ORs 0.55, CI 0.32-0.94), fish (ORs 0.56, CI 0.32-0.98), and fruits (ORs 0.42, CI 0.23-0.79) after adjusting for age. CONCLUSION: To prevent osteoporosis in later life, sufficient Ca intake and more frequent intakes of foods containing Ca such as dairy products, beans, fish, seaweeds, and fruits, which help in Ca absorption, should be stressed for Korean postmenopausal women.